Technology and Innovation of SMEs in Malaysia - Abdul Rani, Nazatul Shima; Myint, Khin (The Edge Solutions, 2010)
In this study, technology management in the areas of competency, adoption, acceptance and innovation are studied in relation to the perspectives from Malaysian SMEs. From the responses received and after analysing the data, it is shown that for technology management, the most important factor, by sequence, would be technology adoption, innovation, technology acceptance and technology competency. As such, in order for SMEs to be able to manage technology, they should focus on technology adoption, whether the technology is able to make the business competitive, increase efficiency, fit the business purpose, fulfil business needs, increase profits, and whether the technology is important for the business. Other than that, should the adopted technology fit the innovation model of the business venture, be accepted by the whole system in the business venture, and is competent enough for the business venture’s need, is considered in order for technology management to be successful for SMEs in Malaysia. As such, this study indirectly produces a process for successful technology management amongst SMEs in Malaysia.